PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA E-LEAFLET TERHADAP PENGETAHUAN IBU HAMIL TRIMESTER I TENTANG KETIDAKNYAMANAN KEHAMILAN - Fyzria Qudratullah; Ria Gustiani; Dona Tri Sundari (LPPM STIKes Mitra Adiguna, 2026)
Discomfort during the first trimester of pregnancy is commonly experienced by pregnant women due to physiological and hormonal changes such as nausea, vomiting, dizziness, fatigue, and emotional changes. Lack of knowledge regarding pregnancy discomfort may lead to anxiety and improper self-care. Health education is an effort to improve pregnant women’s knowledge, one of which is through leaflet media. This study aimed to determine the effect of health education using leaflet media on the knowledge of first trimester pregnant women regarding pregnancy discomfort. This quantitative study used a pre-experimental design with a one-group pretest-posttest approach. The study was conducted at [research location] during [month–year]. The sample consisted of [number] first trimester pregnant women selected using purposive sampling. Data were analyzed using the Wilcoxon test. The results showed a p-value of 0.000 < 0.05, indicating that health education using leaflet media significantly improved pregnant women’s knowledge. Leaflet media is recommended as an effective educational tool in antenatal care services.